Surgeons and preventive health: a mixed methods study of current practice, beliefs and attitudes influencing health promotion activities amongst public hospital surgeons - Stephen Barrett; Stephen Begg; Andrea Sloane; Michael Kingsley (BMC, 2019)
Abstract Background Little is known about the participation of surgeons in preventative health activities in the non-admitted hospital care setting. The aim of this study was to identify which preventive health activities surgeons practice and to explore their attitudes towards preventive health. Methods A mixed methods study was conducted using a sequential explanatory design. Quantitative results were obtained from a self-reported clinician survey (n = 16) and a Generalized Estimating Equation was used to assess the relationship between dependent (preventive health practice) and independent (confidence and knowledge in preventive health practice, years of practice, and attitudinal factors) variables. Using a building approach to integration, results from the quantitative analyses informed design of the interview guide. Surgeons' beliefs and attitudes were explored using in-depth, semi structured interviews with a purposeful sample of surgeons (n = 14). Responses were collected, independently coded and analysed using a qualitative descriptive approach. Results In accordance with a contiguous narrative approach to integration, the quantitative and qualitative findings are reported separately. The clinician survey found that the surgeons carried out preventive health activities at low levels. Preventive health advice was predominantly verbal in nature, and few surgeons provided written material or referred patients to additional services. The GEE analyses indicated that the following factors best predicted the tendency to undertake preventive health activities: years of clinical practice (p = 0.041), and the perceived work priority placed on preventive health (p = 0.008). Interviews generated four themes that influenced the tendency of surgeons to undertake preventive health activities: perceptions of their role in preventive health, perceived motivation of patients, hospital structure, and facilitating factors. In regards to enabling factors that are likely to increase preventive health practice, surgeons unanimously advocated for referral pathways into specialist behaviour change programs that they could facilitate within their relatively brief consulting time. Conclusions The findings suggests that the majority of public hospital surgeons engage in routine preventive health advice at a low level. The high volume of non-admitted surgical consultations undertaken annually, coupled with medium to high self-reported knowledge and confidence in addressing behavioural risk factors, support an increased involvement of surgeons in preventive health practice.